Pressure and compressibility factor of bidisperse magnetic fluids. (14th March 2018) - Minina, Elena S; Blaak, Ronald; Kantorovich, Sofia S
Abstract: In this work, we investigate the pressure and compressibility factors of bidisperse magnetic fluids with relatively weak dipolar interactions and different granulometric compositions. In order to study these properties, we employ the method of diagram expansion, taking into account two possible scenarios: (1) dipolar particles repel each other as hard spheres; (2) the polymer shell on the surface of the particles is modelled through a soft-sphere approximation. The theoretical predictions of the pressure and compressibility factors of bidisperse ferrofluids at different granulometric compositions are supported by data obtained by means of molecular dynamics computer simulations, which we also carried out for these systems. Both theory and simulations reveal that the pressure and compressibility factors decrease with growing dipolar correlations in the system, namely with an increasing fraction of large particles. We also demonstrate that even if dipolar interactions are too weak for any self-assembly to take place, the interparticle correlations lead to a qualitative change in the behaviour of the compressibility factors when compared to that of non-dipolar spheres, making the dependence monotonic.